2018
DOI: 10.1159/000490790
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Method of Measuring Baseline Impedance for Distinguishing Patients with Functional Heartburn from those with Proton Pump Inhibitor-Resistant Endoscopic Negative Reflux Disease

Abstract: Background: Combined 24-h intraesophageal pH-multichannel intraluminal impedance (24MII-pH) used for assessing gastroesophageal reflux disease by measuring baseline impedance (BI) requires a 24-h measuring period. In the present study, we developed a quick method of measuring BI and evaluated its usefulness in classifying patients with proton pump inhibitor (PPI)-refractory non-erosive reflux diseases (NERD) as having functional heartburn (FH) or endoscopic-negative reflux disease (ENRD). Methods: Ninety-one N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“…37 It is crucial to differentiate non-GERD (ie, FH) patients from GERD (ie, erosive esophagitis and non-erosive reflux disease) patients for prescribing different treatments. The MNBI has proven to be useful in distinguishing FH from GERD [14][15][16][17] and FH from RH, 18,19 with a high diagnostic accuracy off-as well as on-PPI therapy (Table 2), and in predicting symptomatic responses to antireflux therapy. [20][21][22][23] However, no study has explored its role in identifying evidence against GERD in patients with refractory GERD symptoms as classified by the Lyon Consensus, which includes evidence against GERD group, conclusive evidence of GERD group, and inconclusive or borderline evidence of GERD group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 It is crucial to differentiate non-GERD (ie, FH) patients from GERD (ie, erosive esophagitis and non-erosive reflux disease) patients for prescribing different treatments. The MNBI has proven to be useful in distinguishing FH from GERD [14][15][16][17] and FH from RH, 18,19 with a high diagnostic accuracy off-as well as on-PPI therapy (Table 2), and in predicting symptomatic responses to antireflux therapy. [20][21][22][23] However, no study has explored its role in identifying evidence against GERD in patients with refractory GERD symptoms as classified by the Lyon Consensus, which includes evidence against GERD group, conclusive evidence of GERD group, and inconclusive or borderline evidence of GERD group.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Mean nocturnal baseline impedance (MNBI) based on MII-pH monitoring is a novel metric that can be obtained manually in a few minutes using a simple formula and has a very high interobserver reproducibility rate. 6,12 It is considered to be a potential objective reflux metric and a marker that reflects longitudinal reflux burden, mucosal integrity, 13 and the severity of esophageal mucosal damage, which has proved to be useful in both separating refluxunrelated (functional heartburn [FH]) patients from reflux-related (GERD [14][15][16][17] and reflux hypersensitivity [RH] 18,19 ) patients and as an independent potential predictor of symptoms responding to antireflux therapy. [20][21][22][23] Low MNBI is adjunctive evidence for inconclusive or borderline evidence for pathologic reflux (AET 4-6%, reflux episodes 40-80, or Los Angeles [LA] A or B), and can increase the impression of conclusive evidence for pathologic reflux.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 15 , 16 , 18 , 19 , 21 28 Lower MNBI values have been found in EE, NERD, and reflux hypersensitivity (RH) compared with FH and healthy controls. 4 , 15 , 16 , 18 , 19 , 21 23 Also, MNBI was significantly lower in patients with refractory reflux esophagitis than in those with healed reflux esophagitis and NERD, indicating that low MNBI could reflect the severity of esophageal mucosal damage. 16 In addition, it has been proved to be useful in distinguishing GERD from healthy controls, 4 , 15 , 21 and distinguishing reflux-related patients (GERD 16 , 18 , 19 , 22 and RH 22 , 23 ) from reflux-unrelated patients (FH) with a high diagnostic accuracy ( Table 2 ).…”
Section: The Utilization Of Mnbi In Patients With Typical Reflux Symp...mentioning
confidence: 99%
“… 33 Moreover, previous studies have demonstrated that MNBI can be useful for distinguishing NERD from FH with high AUC, high sensitivity, and specificity off PPI or on PPI therapy ( Table 2 ). 16 , 18 , 19 , 22 …”
Section: The Utilization Of Mnbi In Patients With Typical Reflux Symp...mentioning
confidence: 99%
“…10 Furthermore, Yoshimine et al reported that a simple method of measuring impedance at one point during the daytime was useful for distinguishing FH from PPIrefractory NERD. 11 The impedance measurement method will continue to be improved.…”
Section: Nonerosive Reflux Diseasementioning
confidence: 99%